2017
DOI: 10.1017/s1368980017002257
|View full text |Cite
|
Sign up to set email alerts
|

Further stabilization and even decrease in the prevalence rates of overweight and obesity in German children and adolescents from 2005 to 2015: a cross-sectional and trend analysis

Abstract: We observed a further stabilization of overweight and obesity prevalence rates for all age groups and even a decrease in the rates for the younger ages (4-7·99 years, 8-11·99 years). As other industrialized countries have also reported similar trends, it seems that the epidemic of childhood overweight and obesity is reaching a turning point in the industrial part of the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 44 publications
1
26
1
Order By: Relevance
“…On the basis of a representative sample of grade 5 children in Alberta, the prevalence of overweight decreased slightly (37.9% to 36.0%) while obesity remained relatively stable (14.2%‐14.6%) across a series of four cross‐sectional surveys from 2008 to 2014 . Other recent studies from high‐income countries have also described decreased or stabilized overweight and obesity in children, suggesting a plateau or reduction in excess weight among sub‐sets of children. Our finding that overweight (in boys and girls) and obesity (in boys only) decreased over time among those children from homes with higher annual incomes highlighted that socio‐economic inequalities moderate excess weight gain early in childhood, even in Alberta, a province that has higher household incomes than other Canadian provinces .…”
Section: Discussioncontrasting
confidence: 97%
“…On the basis of a representative sample of grade 5 children in Alberta, the prevalence of overweight decreased slightly (37.9% to 36.0%) while obesity remained relatively stable (14.2%‐14.6%) across a series of four cross‐sectional surveys from 2008 to 2014 . Other recent studies from high‐income countries have also described decreased or stabilized overweight and obesity in children, suggesting a plateau or reduction in excess weight among sub‐sets of children. Our finding that overweight (in boys and girls) and obesity (in boys only) decreased over time among those children from homes with higher annual incomes highlighted that socio‐economic inequalities moderate excess weight gain early in childhood, even in Alberta, a province that has higher household incomes than other Canadian provinces .…”
Section: Discussioncontrasting
confidence: 97%
“…5.9% were obese (2). Though current trend analysis has shown that prevalence rates of overweight and obesity in children has reached stagnation (3,4), it is important to understand their determinants in order to control the epidemic.…”
Section: Resultsmentioning
confidence: 99%
“…In Germany, according to the German Health Interview and Examination Surveys for Children and Adolescents ("Kinder-und Jugendgesundheitssurvey", KiGGS), 15.4% of children aged 3-17 years were overweight and 5.9% were obese (KiGGS Wave 2, 2014-2017) [2]. Though current trend analysis has shown that prevalence rates of overweight and obesity in children has reached stagnation [3,4], it is important to understand their determinants in order to control the epidemic.…”
Section: Introductionmentioning
confidence: 99%